Direct Numerical Simulation of Twin Swirling Flow Jets: Effect of Vortex-Vortex Interaction on Turbulence Modification. (9th July 2014) - Xu, Wenkai; Gui, Nan; Ge, Liang; Yan, Jie
Abstract : A direct numerical simulation (DNS) was carried out to study twin swirling jets which are issued from two parallel nozzles at a Reynolds number of R e   =   5000 and three swirl levels of S   =   0.68, 1.08, and 1.42, respectively. The basic structures of vortex-vortex interaction and temporal evolution are illustrated. The characteristics of axial variation of turbulent fluctuation velocities, in both the near and far field, in comparison to a single swirling jet, are shown to explore the effects of vortex-vortex interaction on turbulence modifications. Moreover, the second order turbulent fluctuations are also shown, by which the modification of turbulence associated with the coherent or correlated turbulent fluctuation and turbulent kinetic energy transport characteristics are clearly indicated. It is found that the twin swirling flow has a fairly strong localized vortex-vortex interaction between a pair of inversely rotated vortices. The location and strength of interaction depend on swirl level greatly. The modification of vortex takes place by transforming large-scale vortices into complex small ones, whereas the modulation of turbulent kinetic energy is continuously augmented by strong vortex modification.